2011
DOI: 10.1111/j.1469-8986.2011.01181.x
|View full text |Cite
|
Sign up to set email alerts
|

Masked affective stimuli moderate task difficulty effects on effort‐related cardiovascular response

Abstract: This experiment investigated the combined effect of masked affective stimuli and task difficulty on effort-related cardiovascular response. Cardiovascular reactivity (ICG, blood pressure) was recorded during a baseline period and performance of an easy or difficult attention task in which participants were exposed to masked sad vs. happy facial expressions. As expected, participants in the sad-faces/easy and happy-faces/difficult conditions showed stronger sympathetic nervous system discharge to the heart and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
60
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 61 publications
(82 citation statements)
references
References 51 publications
20
60
2
Order By: Relevance
“…not too high however, as successful performance was still possible and justified; if subjective demand was too high, we would have observed low effort exertion due to disengagement (Silvestrini and Gendolla, 2011b). In keeping with an effect of unpleasant-inaction stimuli on motivational processes regulating effort exertion, our fMRI results showed increased activity in regions known to play a role in processing incentive cues and behavioural relevance of sensory events.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…not too high however, as successful performance was still possible and justified; if subjective demand was too high, we would have observed low effort exertion due to disengagement (Silvestrini and Gendolla, 2011b). In keeping with an effect of unpleasant-inaction stimuli on motivational processes regulating effort exertion, our fMRI results showed increased activity in regions known to play a role in processing incentive cues and behavioural relevance of sensory events.…”
Section: Discussionsupporting
confidence: 57%
“…Implicit emotional primes are thought to automatically activate mental representations determining the subjective experience associated with task demands. For example, implicit sadness primes promotes the subjective experience of task difficulty, while happiness primes are associated with ease (Gendolla and Silvestrini, 2011;Silvestrini and Gendolla, 2011b). Together, these studies support the general premise that action-inaction concepts and emotional signals can encourage goal pursuit and modulate effort exertion.…”
Section: Introductionsupporting
confidence: 64%
“…Also in our previous studies on affect priming, we have only sometimes found prime effects on subjective demand ratings (e.g., Gendolla and Silvestrini, 2011;Lasauskaite et al 2013, Lasauskaite Schüpbach et al, 2014Silvestrini and Gendolla, 2011b), or subjective effort (e.g., Chatelain and Gendolla, 2015). Other studies revealed the expected effort effects without significant effects on these self-report measures (e.g., .…”
Section: Discussionmentioning
confidence: 68%
“…Without high incentive, high demand should lead to effort withdrawal due to disengagement. Importantly, previous research has shown that the implicit activation of the difficulty concept by sadness or fear primes during an objectively difficult cognitive task in fact leads to effort withdrawal when no high success incentive is provided (Blanchfield et al, 2014;Lasauskaite Schüpbach et al, 2014;Silvestrini and Gendolla, 2011b). However, high success incentive could eliminate this effort mobilization deficit and boosted effort-related cardiovascular response .…”
Section: Incentive As Moderator Of Age Prime Effects On Effortmentioning
confidence: 99%
“…Positive subliminal cues are thought to decrease the perceived difficulty of a task and consequently reduce effort mobilization (Niedenthal, 2008;Gendolla and Silvestrini, 2011;Silvestrini and Gendolla, 2011;Gendolla, 2012), which may result in decreased performance (Zemack-Rugar et al, 2007). Positive subliminal cues represent a sign that goal pursuit is easy and induce coasting.…”
Section: Introductionmentioning
confidence: 97%